Sejarah perkembangan linguistik - Bella, Silvia Salsa; Jannah, Khilfa Maulidya Nur; Maulidah, Najwa Meia (Maliki Interdisciplinary Journal, 2026)
Linguistics is a science that studies language scientifically, including its structure, function, and use in human life. The problem that often arises is that linguistic understanding is limited to definitions, without a historical understanding of the development of this science, especially in the Western and Arab traditions. This article aims to explain the meaning of linguistics and to describe the history of the development of Western linguistics and Arabic linguistics and the schools and important figures who played a role in them. The research method used is a literature review by examining books, journals, and relevant scientific sources. The results of the study show that Western linguistics developed from Greek philosophy, Greek–Latin grammar, historical-comparative methods, to modern linguistics such as structuralism, generativism, functionalism, and cognitivism. Meanwhile, Arabic linguistics developed along with the need to understand and maintain the purity of the Qur'an, giving birth to important figures as well as two major schools, namely Basrah and Kufa, which had different but complementary approaches. In conclusion, Western and Arabic linguistic developments have different backgrounds and characteristics, but both have made significant contributions to shaping the study of modern linguistics and enriching the understanding of language as a scientific and social phenomenon.